Transnational social protection in Europe: a social inequality perspective. (2nd January 2017) - Faist, Thomas
Abstract: The provision of social protection, especially among migrants, often occurs across the borders of nation-states. More generally, cross-border migration is itself a strategy to reduce risks and threats and may lead to additional employment and social protection. Examining migration is particularly important because it links the disparate, fragmented worlds of unequal life chances and social protection. This analysis asks how efforts to provide social protection for cross-border migrants in the European Union (EU) reinforce existing inequalities (e.g. between regions or within households), and lead to new types of inequalities. Social protection in the EU falls predominantly under the purview of individual member states; hence, frictions between different protection systems and informal social protection are particularly apparent in the case of cross-border flows of people and resources. In order to understand the social protection process, we consider various realms of provision together – state, markets, civil society and families, and formal and informal types of social protection. Using this grid we detail the social mechanisms operative in cross-border forms of social protection, in particular, exclusion, opportunity hoarding, hierarchization, and exploitation.